2014
DOI: 10.1159/000360300
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thoracic Epidural Analgesia on Blood Loss in Radical Retropubic Prostatectomy

Abstract: Introduction: Radical retropubic prostatectomy (RRP) is associated with an increased risk of intraoperative blood loss and the necessity of transfusions. This prospective randomised clinical study evaluates the influence of thoracic epidural analgesia (TEA) on blood loss in RRP. Materials and Methods: 235 patients were randomised: TEA in group 1 (n = 116; general anaesthesia + TEA) comprised continuous administration of 0.25% bupivacaine, while group 2 (n = 119; general anaesthesia alone) received intravenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
4
0
3
Order By: Relevance
“…Hendolin et al [ 18 ] have also shown that the mean perioperative blood loss during operations under epidural analgesia is significantly less than that under general anesthesia (370 ± 34 ml vs. 590 ± 34 ml vs. 590 ± 35 ml). However, another study has reported that the hemoglobin difference between preand the first postoperative day did not show group differences in overall blood loss (general anesthesia + thoracic epidural analgesia: 665 ± 431.5 ml; only general anesthesia: 705 ± 881 ml; P = 0.73) or transfusion rate (0.4% intraoperatively; 2.55% postoperatively; P = 1.0) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hendolin et al [ 18 ] have also shown that the mean perioperative blood loss during operations under epidural analgesia is significantly less than that under general anesthesia (370 ± 34 ml vs. 590 ± 34 ml vs. 590 ± 35 ml). However, another study has reported that the hemoglobin difference between preand the first postoperative day did not show group differences in overall blood loss (general anesthesia + thoracic epidural analgesia: 665 ± 431.5 ml; only general anesthesia: 705 ± 881 ml; P = 0.73) or transfusion rate (0.4% intraoperatively; 2.55% postoperatively; P = 1.0) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has not yet received a satisfactory pathophysiological explanation. A possible explanation for this substantial difference (p = 0.029) could be isoflurane-mediated vasodilation and sympathicolysis, which leads to the widening of blood vessels and thus reduces the opposing venous pressure [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Portanto, tais aspectos devem ser considerados na atenção dispensada ao paciente que, conforme destacam Sena; Nascimento e Maia, (2013), deve ocorrer de forma planejada, individualizada, baseada em evidências científicas, de acordo com o tipo de cirurgia que será realizada e a rotina implementada na instituição.…”
Section: Período Perioperatório: a Recuperação Cirúrgicaunclassified
“…Conforme a literatura, apesar da melhora constante na técnica cirúrgica uma taxa de transfusão de 20-50%, era comum até o início da última década. A perda de sangue pode ser influenciada dentre outros, pela duração da cirurgia (BAUMUNK et al, 2014).…”
Section: Dados Clínicos Do Intraoperatóriounclassified
See 1 more Smart Citation